The Role of Healthcare Access and Maternal Posyandu Adherence on Stunting Incidence on Maratua Island - Fhadillah. Z, Nurul; Rusdi, Rusdi; Rachman, Ainur (International Journal of Health and Pharmaceutical (IJHP), 2026)
Stunting persists as a public health crisis on Maratua Island, Berau Regency, where geographical isolation hinders maternal healthcare access and Posyandu adherence, contributing to high toddler stunting rates despite national efforts targeting below 14% prevalence by 2025. This study aimed to analyze the relationship between maternal healthcare access, Posyandu adherence, and stunting incidence among toddlers. Employing a quantitative descriptive correlational design, it targeted a total population of 54 stunted toddlers from 2025 Puskesmas records using total sampling. Data were collected via structured Likert-scale questionnaires (validity r > 0.268; Cronbach's α > 0.70) combined with anthropometric records, analyzed univariately for characteristics and bivariately via Spearman correlation (SPSS v23) due to non-normal data. Results showed all respondents stunted (mostly mild; 75.9% short stature), with no significant healthcare access correlation (p=0.077) but strong Posyandu adherence link (p=0.000). In conclusion, enhancing maternal Posyandu compliance through targeted island interventions offers greater stunting reduction impact than access improvements alone.